Remedial effects of caffeine against depressive-like behaviour in mice by modulation of neuroinflammation and BDNF. (2nd September 2022) - Basu Mallik, Sanchari; Mudgal, Jayesh; Hall, Susan; Kinra, Manas; Grant, Gary D.; Nampoothiri, Madhavan; Anoopkumar-Dukie, Shailendra; Arora, Devinder
ABSTRACT: Objective: Caffeine (CAF) is one of the most commonly consumed nutritional stimulant in beverages. Interestingly, CAF produces varied effects in a dose-dependent manner, and that makes it one of the most controversial nutritional ingredients. Various studies have linked CAF consumption and reduced risk of depressive disorders. The aim of this study was to investigate the effect of CAF on lipopolysaccharide (LPS)-induced neuroinflammation and depressive-like behaviour. Methods: C57BL/6J male mice were divided into four groups consisting of saline (SAL), LPS, CAF and Imipramine (IMI). Animals were pretreated orally with CAF (10 mg/kg) and IMI (10 mg/kg) for 14 days once daily and all groups except SAL were challenged with LPS (0.83 mg/kg) intraperitoneally on day 14. Results: LPS produced a biphasic behavioural response with a significantly high immobility time and weight loss after 24 h. The brain cytokines (TNF-α, IL-6, IL-1β, and IFN-γ) levels were remarkably high, along with increased lipid peroxidation and reduced Brain Derived Neurotrophic Factor (BDNF). These biochemical and behavioural changes were significantly alleviated by CAF and IMI chronic treatment. Conclusion: The results of this study implicate that mild-moderate consumption of CAF could impart anti-inflammatory properties under neuroinflammatory conditions by modulating the cytokine and neurotrophic mechanisms.